رۆڵی هۆیەكانی فێركردن لەهێنانەدی چەند ئامانجێكی وانەووتنەوەی زمانی كوردی لەڕوانگەی مامۆستایانی بەشی زمانی كوردی - حسین, نظام عبدالجبار (Sulaimani Journal for Humanities, 2018)
The purpose of this research is to find out the role of teaching aids to achieve some of teaching objectives in the Kurdish language from the point of view of Kurdish language teachers.The1٧ research was conducted in Sulaimanyah University / faculty of Basic Education / Department of Kurdish language in (2018) The researcher used the descriptive method as a methodology in his research. The sample of the research was (13) teachers and the questionnaire were used as equipment for its research. The paragraphs of the questionnaire were (18) paragraphs with the used of the statistical methods of (Fischer) and Pearson correlation). Were used and some results were obtained. The results of the questionnaire were above (2) the arithmetic mean, questionnaire sections were positive in the sense that the educational means played huge role in achieving some of teaching objectives. The researcher also presented some suggestions and recommendations with used of some sources related with the research.